Determinasi Brand Trust terhadap Brand Loyalty pada House of Kage Sukabumi - Any Octaviany; Nor Norisanti; Dicky Jhoansyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
Brand loyalty is one concept that plays a very important role in marketing strategies to maintain customers who are loyal to the brand. The purpose of this research is to explain the influence of bran reliability and brand intention as brand trust’s dimension on brand loyalty in the Muslim clothing House Of KAGE Sukabumi. Tehe method that use in this research is descriftive associative and quantitative approaches with multiple linear regression as a data analysis technique. Result of the research shows that the magnitude of the influence of brand trust on brand loyalty in the Muslim clothing House Of KAGE after testing simultaneously and partially have a positif and significant influence. It’s amounted to 11.8%, while the remaining 88.2% are influenced by other variables not examined in this research. Keyword : Brand Trust, Brand reliability, Brand intention, Brand Loyalty.